2008
DOI: 10.1210/me.2007-0512
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Regulates Snail and Slug in the Down-Regulation of E-Cadherin and Induces Metastatic Potential of Ovarian Cancer Cells through Estrogen Receptor α

Abstract: Tumorigenesis is a multistep process involving dysregulated cell growth and metastasis. Considerable evidence implicates a mitogenic action of estrogen in early ovarian carcinogenesis. In contrast, its influence in the metastatic cascade of ovarian tumor cells remains obscure. In the present study, we showed that 17beta-estradiol (E2) increased the metastatic potential of human epithelial ovarian cancer cell lines. E2 treatment led to clear morphological changes characteristic of epithelial-mesenchymal transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
176
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(192 citation statements)
references
References 68 publications
12
176
1
3
Order By: Relevance
“…For example, TWIST1, TWIST2, HDAC6, MUC1, ETS2, NFkB, Jun, SP1 , and AP1 were previously reported as enhancers of EMT, and were found activated in postEMT cells. Other TFs, such as ER, SPDEF , and HMGA1 , were previously reported as repressors of EMT, and were found repressed in this study 18, 19, 20. Interestingly, SMAD7 was previously reported as an EMT repressor; we found that SMAD7 gene expression was consistently elevated after EMT induction and positively correlated with postEMT 21.…”
Section: Resultssupporting
confidence: 65%
“…For example, TWIST1, TWIST2, HDAC6, MUC1, ETS2, NFkB, Jun, SP1 , and AP1 were previously reported as enhancers of EMT, and were found activated in postEMT cells. Other TFs, such as ER, SPDEF , and HMGA1 , were previously reported as repressors of EMT, and were found repressed in this study 18, 19, 20. Interestingly, SMAD7 was previously reported as an EMT repressor; we found that SMAD7 gene expression was consistently elevated after EMT induction and positively correlated with postEMT 21.…”
Section: Resultssupporting
confidence: 65%
“…Silencing of either Snail or Slug caused reversion of the mesenchymal-like phenotype, and in addition treatment with the oestrogen antagonist ICI was shown to overcome the inhibitory effect of E 2 on E-cadherin transcription, suggesting a crucial role for oestrogen and its receptor in EMT-dependent tumour progression. Interestingly, in the same study it was also demonstrated that presence of ERb had an opposing effect on ERa, in the context of EMT regulation, inhibiting the ERa-induced EMT (Park et al, 2008). These findings may explain the mechanism by which ER status regulates invasion and metastasis in breast cancer.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, aetiological factors such as, for example, age at first full-term pregnancy, affects the importance of Snail as a susceptibility marker, and single-nucleotide polymorphism (SNP) of Snail has been shown to be of importance for the oestrogen-related risk factor in relation to breast cancer risk (Yu et al, 2006). In one study it was demonstrated that 17b-estradiol (E 2 ) treatment, in an ERa mediated manner, resulted in increased metastatic potential, morphological changes characteristic of EMT and increased transcriptional activity of the Snail and Slug genes, accompanied by decreased levels of E-cadherin in an ovarian cancer cell line (Park et al, 2008). Silencing of either Snail or Slug caused reversion of the mesenchymal-like phenotype, and in addition treatment with the oestrogen antagonist ICI was shown to overcome the inhibitory effect of E 2 on E-cadherin transcription, suggesting a crucial role for oestrogen and its receptor in EMT-dependent tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…*P<0.05 vs. control. Representative images of at least three independent experiments are shown other studies [24]. We analyzed phenotypical changes around the wound area, including wound shape, MCF-7 cell morphology, intercellular separation, formation of pseudopodia, and cytoskeletal dynamics of F-actin (Fig.…”
Section: E2 Promotes Mcf-7 Migration In Vitromentioning
confidence: 99%